The Influence of Internal Control System, Individual Morality, and HR Competency on Fraud Prevention with Good Governance as An Intervening Variables: Study on OPD Deli Serdang Regency, North Sumatra - Ananda Sabrida Tora Br Sinaga; Rina Br Bukit; Rujiman Rujiman (LPPM Universitas Jambi, 2021)
This study aims to determine the effect of internal control systems, individual morality, and human resource competence on fraud prevention at OPD Deli Serdang Regency. In addition, this study also aims to determine whether good governance is able to mediate the effect of the internal control system on fraud prevention in OPD Deli Serdang Regency. This type of research is a causal associative research. This study uses a quantitative approach. This research was conducted on all OPDs (Regional Apparatus Organizations) in the Deli Serdang Regency Government. The sample in this study amounted to 83 people. While the data analysis technique used is PLS (Partial Least Square) with the help of SmartPLS software which is run on computer media. The results found in this study indicate that the internal control system has a positive and significant effect on fraud prevention in OPD Deli Serdang Regency. Individual morality has a positive and significant effect on fraud prevention. HR competencies do not have a significant effect on fraud prevention. Good governance is able to mediate the influence of the internal control system on fraud prevention. Good governance is able to mediate the effect of individual morality on fraud prevention. Meanwhile, good governance is not able to mediate the effect of HR competence on fraud prevention in OPD Deli Serdang Regency.